Direct Comparison of 19F qNMR and 1H qNMR by Characterizing Atorvastatin Calcium Content - Yang Liu; Zhaoxia Liu; Huaxin Yang; Lan He (Journal of Analytical Methods in Chemistry)
Quantitative nuclear magnetic resonance (qNMR) is a powerful tool in measuring drug content because of its high speed, sensitivity, and precision. Most of the reports were based on proton qNMR (1H qNMR) and only a few fluorine qNMR (19F qNMR) were reported. No research has been conducted to directly compare the advantage and disadvantage between these two methods. In the present study, both 19F and 1H qNMR were performed to characterize the content of atorvastatin calcium with the same internal standard. Linearity, precision, and results from two methods were compared. Results showed that 19F qNMR has similar precision and sensitivity to 1H qNMR. Both methods generate similar results compared to mass balance method. Major advantage from 19F qNMR is that the analyte signal is with less or no interference from impurities. 19F qNMR is an excellent approach to quantify fluorine-containing analytes.